Ter gelegenheid van het officiële bezoek van de minister van Binnenlandse Zaken, I.E. Drs. Catharina Isabella Dales
Ter gelegenheid van het officiële bezoek van de minister van Binnenlandse Zaken, I.E. Drs. Catharina Isabella Dales.